The effect of shade tree species on bird communities in central Kenyan coffee farms. Issue 4 (17th December 2022) - KAMMERICHS-BERKE, DEVEN; LANE, FANTER J.; ONG'ONDO, FRANK JUMA; MLAMBA, EDSON M.; BEAN, WILLIAM T.; JEDLICKA, JULIE A.; NJOROGE, PETER; JOHNSON, MATTHEW D.
Summary: Shade coffee is a well-studied cultivation strategy that creates habitat for tropical birds while also maintaining agricultural yield. Although there is a general consensus that shade coffee is more "bird-friendly" than a sun coffee monoculture, little work has investigated the effects of specific shade tree species on insectivorous bird diversity. This study involved avian foraging observations, mist-netting data, temperature loggers, and arthropod sampling to investigate bottom-up effects of two shade tree taxa - native Cordia sp. and introduced Grevillea robusta - on insectivorous bird communities in central Kenya. Results indicate that foliage-dwelling arthropod abundance, and the richness and overall abundance of foraging birds were all higher on Cordia than on Grevillea. Furthermore, multivariate analyses of the bird community indicate a significant difference in community composition between the canopies of the two tree species, though the communities of birds using the coffee understorey under these shade trees were similar. In addition, both shade trees buffered temperatures in coffee, and temperatures under Cordia were marginally cooler than under Grevillea. These results suggest that native Cordia trees on East African shade coffee farms may be better at mitigating habitat loss and attracting insectivorous birds that could promote ecosystem services. Identifying differences in prey abundance and preferences in bird foraging behaviour not only fills basic gaps in our understanding of the ecology of East African coffee farms, it also aids in developing region-specific information to optimize functional diversity, ecosystem services, and the conservation of birds in agricultural landscapes.